№1
a) (2x - 1)² = 4x² - 4x + 1
б) (3a + c)² = 9a² + 6ac + c²
в) (y-5)(y+5) = y² - 25
г) (4b + 5c)(4b - 5c) = 16b² - 25c²
№2
(x + y)(x - y) - (x² + 3y²) =
x² -y² -x² - 3y² =
-y² - 3y² =
-4y²
№3
а) 16y² - 0,25 = 0,25 (64y² - 1) = 0,25 (8y - 1)(8y + 1)
б) a² + 10ab +25b² = (a + 5b)²
№4
(5 - x)² - x(2,5 + x) = 0
25 - 10x + x² - 2,5x +x² = 0
25 - 12,5x = 0
-12,5x = -25
x = 2
№5
a) (2a - b²)(2a + b²) = 4a² -
б) (x-6x³)² = 36 - 12 + x²
в) (y + b)²(y - b)² = ((y + b)(y - b))² = (y² - b²)² = - 2b²a² +
№6
а)
б)
в)
№1
a) (2x - 1)² = 4x² - 4x + 1
б) (3a + c)² = 9a² + 6ac + c²
в) (y-5)(y+5) = y² - 25
г) (4b + 5c)(4b - 5c) = 16b² - 25c²
№2
(x + y)(x - y) - (x² + 3y²) =
x² -y² -x² - 3y² =
-y² - 3y² =
-4y²
№3
а) 16y² - 0,25 = 0,25 (64y² - 1) = 0,25 (8y - 1)(8y + 1)
б) a² + 10ab +25b² = (a + 5b)²
№4
(5 - x)² - x(2,5 + x) = 0
25 - 10x + x² - 2,5x +x² = 0
25 - 12,5x = 0
-12,5x = -25
x = 2
№5
a) (2a - b²)(2a + b²) = 4a² -![b^4](/tpl/images/1103/6123/7ffa9.png)
б) (x-6x³)² = 36
- 12
+ x²
в) (y + b)²(y - b)² = ((y + b)(y - b))² = (y² - b²)² =
- 2b²a² +![b^4](/tpl/images/1103/6123/7ffa9.png)
№6
а)![\frac{1}{81}a^{2} - 0,09c^4 = \frac{1}{81}a^{2} - \frac{9}{100} c^4 = \frac{1}{8100}(100a^2 - 729c^4) = \frac{1}{8100}(10a - 27c^2)(10a + 27c^2)](/tpl/images/1103/6123/0179c.png)
б)![(b + 8)^2 - 4b^2 = (b+8-2b)(b+8+2b) = (-b+8)(3b+8)](/tpl/images/1103/6123/e2ec9.png)
в)![a^9 - b^3 = (a^3 - b)(a^6 + a^3b + b^2)](/tpl/images/1103/6123/0e2ac.png)